DECIPHERING THE IMMUNE LANDSCAPE OF OVARIAN CANCER: AN IN-DEPTH ANALYSIS OF IGCH CD4+, CD8+, AND PD-L1 IN TUMOR MICROENVIRONMENT AND THEIR THERAPEUTIC IMPLICATIONS - Ulmasov, Firdavs; Mamarasulova, Dilfuzakhon; Esankulova, Bustonoy (Medical science of Uzbekistan, 2025)
Relevance. Ovarian cancer is one of the most lethal gynecological malignancies worldwide, with high mortality primarily due to late-stage diagnosis and the lack of effective early screening. The tumor microenvironment (TME) plays a crucial role in cancer progression, immune evasion, and resistance to therapy. Immune cells, particularly CD4+ and CD8+ T cells, along with immune checkpoint proteins like PD-L1, significantly influence tumor behavior and therapeutic response. Understanding their roles in ovarian cancer may provide insights into novel immunotherapeutic strategies. Materials and methods of study. A total of 135 ovarian cancer patients from the Republican Specialized Scientific and Practical Medical Center of Oncology and Radiology, Samarkand Branch, were included in this study. Tumor samples were obtained through biopsy or surgical resection, and immune profiling was performed using multiplex immunohistochemistry and flow cytometry. The expression levels of CD4+, CD8+, and PD-L1 were quantified, and their spatial distribution within the TME was analyzed. Correlations between immune profiles and clinical outcomes, including survival rates and response to immunotherapy, were assessed. Research results. CD4+ T helper cells exhibited functional diversity, with Th1 cells promoting anti-tumor immunity, whereas Th2 and regulatory T cells (Tregs) contributed to immune suppression in advanced tumors. High CD8+ T-cell infiltration correlated with improved survival; however, elevated PD-L1 expression was associated with T-cell exhaustion (PD-1, TIM-3, LAG-3) and immune evasion. Increased PD-L1 levels were linked to poor prognosis, reinforcing its role as a key immune checkpoint regulator. Conclusion. This study highlights the prognostic significance of CD4+, CD8+, and PD-L1 expression in ovarian cancer. Immune profiling may aid in personalized treatment strategies, optimizing immunotherapy efficacy. Future research should focus on integrating multi-omics approaches to enhance patient stratification and improve therapeutic outcomes.